ADMINISTRATIVE COMMUNICATION STRATEGIES IN HYBRID WORK ENVIRONMENTS - Aghus Jamaludin Kharis (Penelitian dan Pengembangan Ilmu, 2025)
The post-COVID-19 pandemic hybrid work model, combining face-to-face and virtual interactions, demands adaptive, transparent, and structured administrative communication strategies. This study uses a narrative review to examine the literature related to administrative communication strategies and their impact on the effectiveness of hybrid organizations. Findings indicate that channel strategy (synchronous/asynchronous), communication style adaptation, and transparency and clarity play a crucial role in building trust, increasing engagement, facilitating coordination, and accelerating decision-making. Communication theories such as Media Richness Theory and Organizational Information Theory are relevant for media selection and information management. Key challenges include miscommunication, digital fatigue, and technology access gaps. This study expands the theoretical understanding of administrative communication as a strategic function and provides practical guidance for managers. Suggestions for future research include empirical studies, cross-cultural comparisons, and AI integration.